Anisakis spp. as indicators of latitudinal movements of short‐finned pilot whales, Globicephala macrorhynchus , in the Northeast Atlantic - Claudia Pons‐Bordas; Rachel V. Pool; Sofía Ten; José A. Armenteros‐Santos; Ana Balseiro; Manena Fayos; F. Javier Aznar (Marine Mammal Science, 2025)
In the Northeast Atlantic, it is unclear whether short‐finned pilot whales, Globicephala macrorhynchus (SFPWs), are transient or resident above 40°N. We used Anisakis spp. to identify the latitudes recently visited by a SFPW pod stranded in NW Spain (43°N) in 2020. Analysis of cox2 gene in 30 nematodes from 6 SFPWs revealed the presence of A. simplex sensu stricto (s.s.) (93.3%) and A. pegreffii (6.7%). Morphological analysis of 972 nematodes corroborated species molecular identification and relative proportions; in males ( n = 66), the estimated proportions of A. simplex s.s. and A. pegreffii were 86.4% and 13.6%, respectively. These percentages resembled those reported in fish/cetaceans above 40°N, and L4 larvae or adults of A. typica (a tropical‐temperate species found in SFPWs up to 38°N–39°N) were not detected. Population structure of A. simplex s.s. + A. pegreffii in SFPWs suggested a continuous recruitment of nematodes starting at least 3 weeks before stranding. We interpret that either the SFPW pod was within the range of the species (perhaps as a recent northern shift) or represented a vagrant group that visited waters off Northwest Spain for a protracted period. Future analysis on nematode assemblages could shed light on movements and climate‐driven shifts in cetacean distribution.

Fine‐scale distribution of the lungworm Halocercus delphini in the lungs of the striped dolphin, Stenella coeruleoalba : implications about migration pathways and functional significance - Rachel V. Pool; Neus Pons‐García; Francesco Consoli; Miguel Rivero; Cristiano Bombardi; Juan A. Raga; Francisco J. Aznar (Marine Mammal Science, 2024)
Despite their high pathogenicity, limited knowledge is available on intrahost migration pathways and microhabitat distribution of pseudaliid lungworms. In this study, the distribution of Halocercus delphini in the lungs of the striped dolphin, Stenella coeruleoalba , was analyzed on three scales: between the right and left lungs, within the lungs, and between worm clusters. Evidence of a relationship between the distribution of H. delphini and the perfusion of the lungs of S. coeruleoalba is provided by the consistent correlation of these two factors, both on a longitudinal scale and by the difference in parasite burden between the left and right lung. This relationship, when coupled with the nested pattern of colonization, suggests that this species, like many other metastrongyloids, migrates to the lungs via the circulatory system. Additionally, the concentration of lungworms around the major airways could be a further reflection of the well‐perfused nature of these passageways. Equally, this distribution could be a strategy to minimize the distance that larvae must travel to exit the lungs via the trachea, as do most other metastrongyloids. On a more localized scale, the tendency of H. delphini to form distinct heterosexual clusters even at low infection intensities indicates active mate‐seeking behavior for reproduction.